2014
DOI: 10.3892/etm.2014.1487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroxin and donepezil on hippocampal acetylcholine content and syntaxin-1 and munc-18 expression in adult rats with hypothyroidism

Abstract: Adult-onset hypothyroidism induces various impairments in hippocampus-dependent cognitive function, in which numerous synaptic proteins and neurotransmitters are involved. Donepezil (DON), an acetylcholinesterase inhibitor, has been shown to be efficient in improving cognitive function. The aim of the present study was to investigate the effects of adult-onset hypothyroidism on the expression levels of the synaptic proteins syntaxin-1 and munc-18, as well as the content of the neurotransmitter acetylcholine (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…Although many neurotransmitter systems like GABAergic, glutaminergic and dopaminergic have been shown to be affected by thyroid hormone imbalance, the cholinergic system is the most strongly affected indicating a very close functional association between TH and cholinergic function [29,31,48]. Acetylcholine is metabolized into Acetyl-CoA and choline by the enzyme AChE, the activity of which has been recently shown to be directly affected by thyroxin [35]. The predominant AChE isoforms in brain are the monomeric, salt soluble (SS) G1 and the tetrameric, detergent soluble (DS) G4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many neurotransmitter systems like GABAergic, glutaminergic and dopaminergic have been shown to be affected by thyroid hormone imbalance, the cholinergic system is the most strongly affected indicating a very close functional association between TH and cholinergic function [29,31,48]. Acetylcholine is metabolized into Acetyl-CoA and choline by the enzyme AChE, the activity of which has been recently shown to be directly affected by thyroxin [35]. The predominant AChE isoforms in brain are the monomeric, salt soluble (SS) G1 and the tetrameric, detergent soluble (DS) G4.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of current studies, revealing TH along with AChE inhibitors as a combined pharmacological treatment of hippocampus synaptic protein impairment induced by adult onset hypothyroidism [35], the aim of the present study was to comprehensively investigate the effects of adult onset hypothyroidism on learning/memory and fear/anxiety behavior and on the activity of two different AChE isoforms in five different brain regions of adult male Balb/cJ mice. Although most relevant reports focus on cerebral hemispheres and hippocampus, we expand the current knowledge by investigating concomitantly cerebellum, midbrain and striatum along with cerebral hemispheres and hippocampus since our previous publications strongly suggest that cholinergic system function of all these brain regions affects differentially learning/memory and fear/anxiety behavior [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous clinical studies have indicated that patients with hypothyroidism who were properly treated with T4 have not always fully recovered from the symptoms affecting the central nervous system, such as the cognitive functioning and well-being ( 16 18 ). Previous animal studies of the authors have revealed that hypothyroidism induces significant expression changes of several synaptic proteins in the brain regions related to learning and memory, whereas some of the proteins were not fully restored to control values by T4 treatment ( 13 , 14 , 19 ). Furthermore, in previous morphological studies, Madeira et al ( 20 , 21 ) discovered that hypothyroidism induces reductions in the number of pyramidal cells in the hippocampal CA1 region and granule cells in the dentate gyrus, which were also not restored following the normalization of thyroid hormone levels in adult rats.…”
Section: Introductionmentioning
confidence: 84%
“…The total treatment time was two weeks. The dose of T4 was selected based on previous studies ( 14 , 19 ), and the dosage was adjusted according to the rats' weights weighed weekly.…”
Section: Methodsmentioning
confidence: 99%